ANALISIS KINERJA PEGAWAI DINAS PENDIDIKAN DAERAH PROVINSI SULAWESI TENGAH DALAM PEMBERIAN BANTUAN KHUSUS MURID MANDIRI PADA SMA/SMK DI KOTA PALU - Altar, Altar (Katalogis, 2013)
This research aims: 1) at finding out and analyzing Staffâ€™s Performance Of Provincial Education Office Of Central Sulawesi In Providing Special Help Of Independent Students At Sma/Smk In Palu, and 2). At identifying what factors that restrict the Staffâ€™s Performance Of Provincial Education Office Of Central Sulawesi In Providing Special Help Of Independent Students At Sma/Smk In Palu. This is a qualitative research, interviews using porpusive sampling, chosen by taking into consideration and specific pupose by the head of secondary education affairs (DIKMENTI), the head of senior high school guidance section, the head of vocational high school guidance section, the staff of secondary education affairs, and the principals of senior high and vocational high school. The writer used the theory (Dwiyanto, 1995:6) of Productivity, quality, responsiveness, responsibility and accounability. The techniques of data collection were observation, interview and documentation. It is found that firstly, theÂ Productivity, showing the level of each staffâ€s understanding in providing special aid to the independent students of SMA/SMK at the Provincial Education and instruction office of central sulawesi province, is effective enough; secondly, the quality of service is that there are staff, responsible for providing special aid to the independent students, who often ignore their job or do another job; thirdly, responsiveness shows that there are complaints from the schools relating to the distribution of special aid to the independent student at the Provincial Education and Instruction Office of Central Sulawesi Province, and less optimality of catering for the studentsâ€™ needs; and fourthly, responsibility is, looking at the ease in forwarding the case and assessing the documents proposed by the school that is going to receice special aid to the independent students, less maximal.